Claiming Social and Cultural Dignity: Isabella Andreini's Rime. (3rd July 2022) - Riverso, Nicla
ABSTRACT: Isabella Andreini strove to establish a public image as a woman who, though an actress, was also a pious, virtuous, and learned writer. She showed that it was possible to perform on stage and, at the same time, embody the Christian values promoted by the Counter-Reformation Church. Andreini was well aware that although she was a talented actress, dancer, singer, and musician, earning respect as an honourable woman and receiving the recognition of posterity would depend on self-elevation through her writing. This essay reflects on Andreini's critically under-investigated Rime, with a particular focus on those written in a religious vein, in order to demonstrate how the actress used her literary skills to emphasise her image as a virtuous woman. These skills brought her prestige and literary immortality, but they also helped her to claim social and cultural dignity for herself, for her profession, and for the women of her age.